EFEK ANTI PROLIFERATIF EKSTRAK ETANOL KULIT BATANG TANAMAN CANGKRING (Erythrina fusca Lour) TERHADAP SEL MYELOMA - Meiyanto, Edy; Sismindari, Sismindari; Triastuti, Asih (Jurnal Ilmiah Farmasi, 2004)
ABSTRACTErythrina fusca Lour has been traditionally used to cure hepatosis, malaria, hematuria, andcancer. The bark of this plant contains  carotene, polifenol, thiamin, saponin, and alkaloiderythralin and erythramin. The aim of this research was to know the underlying mechanism of itseffect as antiproliferative against Myeloma cells. The bark powder was extracted using ethanol(70%) and was used for the experiment after freezed drying. Citotoxicity test of this extractperformed LC50 of 0,367 mg/ml. The rate of proliferation was observed by doubling time effectagainst proliferating cells. The cells were exposed with ethanolic extract in RPMI 1640 mediumcontaining 1) 0,25 mg/ml 2) 6,25x10-2mg/ml, and 3) 1,56x10-2mg/ml and every 0, 6, 12, 24, 48,and 72 hours cell were counted. The result showed that extract treated cells delayed proliferation atall concentration with doubling time dose 2) of 161, 38 hours, and dose 3) of 93,91 hours, whereasdoubling time of control cells were 69,86 hours. Ethidium bromide staining of extract treated cellsshowed apoptosis like profile. These results indicated that ethanolic extract of the bark of Erythrinafusca Lour has an antiproliverative effect on Myeloma cell line. Several mechanisms might accountfor this effect, like inhibiting cell cycle progression, signal transduction, causing delayed andapoptosisKeywords: Erythrina fusca Lour, atiproliferative, Myeloma